FORGING A PATH FORWARD: SAFEGUARDING INDIGENOUS COMMUNITIES FROM THE IMPACT OF CLIMATE CHANGE - Allyana, Olivia; Indriyani, Rachma (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This article examines the effects of ‘climate change’ on indigenous communities and the safeguarding of their rights, with a focus on the “Daniel Billy et.al v. Australia” case ‘climate change’ poses severe threats to ‘indigenous peoples’' livelihoods and traditions, yet they also contribute significantly to mitigating its impacts. Utilizing normative legal research methods, including statutory and case law analysis, it evaluates the protection of indigenous rights by the UNHRC. The analysis highlights the significance of the “UNHRC”'s decision in “Daniel Billy et.al v. Australia”, which represents a milestone in international law regarding ‘climate change’ 's repercussions on human rights. While non-binding, the ruling grants access and establishes a crucial precedent for enforcing indigenous claims against states failing to safeguard their rights. It has influenced national legal frameworks and guided interpretations of indigenous rights. Considering subsequent practices in applying human rights treaties and utilizing “UNHRC” rulings as interpretive aids are essential. This analysis aims to deepen comprehension of the challenges and prospects in safeguarding the rights of climate-affected indigenous populations on the global stage. The scholarly contribution of research can be articulated through its novel engagement with the intersection of climate change, indigenous rights, and international human rights law, particularly through the lens of the Daniel Billy et al. v. Australia case before the UN Human Rights Committee (UNHRC)